Analysis of Science Process Skills for Student in Basic Physics Course - Saparini Saparini; Nely Andriani; Abidin Pasaribu (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2019)
The low cognitive learning outcomes and science process skills of students encourage the need for learning that not only emphasizes learning outcomes but also the learning process. The purpose of the research is to (1) find out the profile of science process skills of students when attending basic physics practicum lectures, and (2) to find out the most dominant science process skills in students while attending basic physics practicum lectures. The research method used is descriptive method with a qualitative approach. The subject of this study was chosen by purposive sampling and obtained by students of the 2017/2018 academic year Physics Education study program FKIP Sriwijaya University. The research data was collected using documentation techniques, observation, and interviews. The data obtained is then processed through the stages of data reduction, data presentation, data analysis, and conclusion drawing. Data analysis was carried out descriptively, so as to increase trust in the results of the study triangulation of data collection techniques was conducted. The research that has been done obtained results that (1) science process skills of students while following the basic physics practicum lectures in the high category that is equal to 68.1%; (2) the dominant science process skills namely observing skills of 91.0% are very high categories and measure 91.1% in very high categories. The results of the study illustrate that the implementation of basic physics practicums still needs improvement to train students' science process skills.